Revitalization of Pancasila Economic System in the Globalization Era - Waspodo Tjipto Subroto (International Journal of Economics and Financial Issues, 2015)
Implementation of the policy will effect the economic system of economic growth and prosperity of a nation. Follow the globalization of economic liberalization is detrimental to most of the people of Indonesia for the door wide open to free competition so it is very unfortunate that the developed countries are relatively better equipped to compete because it is supported by financial capital and modern technology. For socializing Pancasila economic system, there needs revitalization movement Pancasila economic system in a more systematic and planned so that the system is able to host in his own country. Revitalization of Pancasila economic system needs to be pursued constantly and sustained through the implementation of economic policies in favour of the people and to anticipate the growing influence of economic globalization and spread to various world. Revitalization is expected to bring the Indonesian people toward the common good in adapting to the era of globalization.